MINAT BERWIRAUSAHA MAHASISWA SELAMA PANDEMI: APAKAH PENDIDIKAN KEWIRAUSAHAAN DAN EKSPEKTASI PENDAPATAN BERPENGARUH? - Serly Octavia Privana; Putri Ulfa Kamalia (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The unemployment rate increased significantly in Indonesia in time covid-19 pandemic, so that the role of students with entrepreneurial education insight is needed to be a agent of change by creating various job opportunities through entrepreneurship. The purpose of this study was to determine the effect of entrepreneurship education and income expectations on student entrepreneurship interest during this pandemic. With the research subjects  of 2018 Unesa Economics Education Departement students and a sample of 153 students. This study uses primary data obtained from questionnaires. This method of analysis used multiple linear regression analysis. The result of this study are 1) there is a positive and significant influence between the entrepreneur education variable and the entrepreneur's preference variable 2) there is a  significant positive influence between the income expectation variable for with business interests 3) there is a  positive effect between the entrepreneurship training variable and the income expectation variable on the interest in entrepreneurship among students of the Faculty of Economic Education at Unesa.